Predicting risk of obesity in overweight adults using interpretable machine learning algorithms - Lin, Wei; Shi, Songchang; Huang, Huibin; Wen, Junping; Chen, Gang (Frontiers in Endocrinology, 2023)
Objective: To screen for predictive obesity factors in overweight populations using an optimal and interpretable machine learning algorithm.Methods: This cross-sectional study was conducted between June 2011 and January 2012.The participants were randomly selected using a simple random sampling technique. Seven commonly used machine learning methods were employed to construct obesity risk prediction models. A total of 5,236 Chinese participants from Ningde City, Fujian Province, Southeast China, participated in this study. The best model was selected through appropriate verification and validation and suitably explained. Subsequently, a minimal set of significant predictors was identified. The Shapley additive explanation force plot was used to illustrate the model at the individual level.Results: Machine learning models for predicting obesity have demonstrated strong performance, with CatBoost emerging as the most effective in both model validity and net clinical benefit. Specifically, the CatBoost algorithm yielded the highest scores, registering 0.91 in the training set and an impressive 0.83 in the test set. This was further corroborated by the area under the curve (AUC) metrics, where CatBoost achieved 0.95 for the training set and 0.87 for the test set. In a rigorous five-fold cross-validation, the AUC for the CatBoost model ranged between 0.84 and 0.91, with an average AUC of ROC at 0.87±0.022. Key predictors identified within these models included waist circumference, hip circumference, female gender, and systolic blood pressure.